ALGORITMA PENJADWALAN ULANG PADA INDUSTRI KIMIA PROCESS BATCH SPACE 1 DAN SPACE 2 - Hartini, Sri
Abstrak : Short term scheduling of batch process chemical production system is a vital issues because of its dynamic behaviour, process variability and complexities. Scheduling system in discrete type production system cannot apply directly to batch process, because of the specific characteristic. Batch process management, therefore, requires a new on-line scheduling framework based on the characteristic of batch process. Batch chemical plants are classified into two categories : multiproduct and multipurpose. In multiproduct plant, all products follow essentially the same sequence of processing step. In multipurpose plant, the products may follow different paths through the plant [Ku et al, 1987]. Ishii and Muraki (1997) developed a generic framework for on-line scheduling and control system (FOSS) in batch process management, which proposed three spaces of rescheduling action, which ar : space 1 : modification in the task start and completion times, space 2 :modifi cation of resource assignment without changing the production sequence, and space 3 : change the production sequence. But FOSS has not been developed a detail algorithm, thus FOSS need a detail algorithm for each space. This research proposes algorithm for space 1 and space 2. in multiproduct batch prosess based on the ON of disruption occurred, i.e.: processing time variation, changes of unit availability and operator availability. Developing of the algorithm considered type of waiting time contrains, Zero wait (ZW) and UW (Unlimited Wait)